2007
DOI: 10.2215/cjn.03941106
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Preference Scores in Conventional and Home Nocturnal Hemodialysis Patients

Abstract: Previous studies have reported higher quality of life in patients who receive home nocturnal hemodialysis (HNHD) than conventional in-center hemodialysis (IHD). The optimal method for eliciting preferences from dialysis patients remains undefined, and there may be unique methodologic concerns in this population. Patients' preferences for IHD (n ‫؍‬ 20) and HNHD (n ‫؍‬ 24) were studied using the standard gamble (SG), time trade-off (TTO), and modified willingness to pay (WTP) methods. This report describes expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…20,21 Improved quality of life Findings from many observational cohort studies suggest that patients' QOL is better on IHHD than on incentre CHD. [22][23][24][25][26] Furthermore, in a systematic review of 197 patients from 13 HHD programs, a consistent improve ment in QOL was demonstrated for patients receiving IHHD versus those receiving incentre CHD, although the included studies were not of consistently high quality. 27 QOL for patients receiving home NHD has also been evaluated in two RCTs.…”
Section: Improved Survivalmentioning
confidence: 99%
“…20,21 Improved quality of life Findings from many observational cohort studies suggest that patients' QOL is better on IHHD than on incentre CHD. [22][23][24][25][26] Furthermore, in a systematic review of 197 patients from 13 HHD programs, a consistent improve ment in QOL was demonstrated for patients receiving IHHD versus those receiving incentre CHD, although the included studies were not of consistently high quality. 27 QOL for patients receiving home NHD has also been evaluated in two RCTs.…”
Section: Improved Survivalmentioning
confidence: 99%
“…The quality of life of patients receiving dialysis is amongst the worst reported for any chronic medical condition (8). Utility scores rank quality of life on a scale from 0 (the worst imaginable quality of life, often equated to death) and 1 (the best imaginable quality of life) (9,10). Utility scores on conventional HD are typically in the range of about 0.5, while utility scores in people with a working kidney transplant tend to be significantly higher in the 0.7 range (8,11,12).…”
Section: Quality Of Lifementioning
confidence: 99%
“… 5 , 6 , 7 , 8 For patients who are unable to or are waiting to receive a kidney transplant, extended hours of home hemodialysis is associated with clinical and quality-of-life outcomes that are closer to transplantation than other dialysis modalities. 9 , 10 , 11 , 12 , 13 , 14 …”
mentioning
confidence: 99%